DEVELOPING STUDENTS’ INTEREST THROUGH PEDAGOGICAL TOOLS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The problem of educating students' interest in learning is one of the main didactic problems. Current problems of theory and practice of education are among the main directions of development of integrated pedagogical process in higher education, increasing interest in knowledge of the studied subject, activation of students' educational activities. It is inextricably linked with the education system, the upbringing of a person and the formation of his basic culture.